Rheological Properties of Wheat Flour (Triticum aestivum L.) Doughs as Affected by Inclusion of Decorticated Pigeon pea (Cajanus cajan L.) Flour and Protein Isolate - Hassan, Hayat A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The objective of this study was to investigate the rheological properties of wheat flour (Triticum aestivum L.) doughs affected by the incorporation of decorticated pigeon pea (Cajanus cajan L.) flour (DPPF) and pigeon pea protein isolate (PPPI) aiming the production of bakery products. Ratios of DPPF (0, 5, 10, 15, 20 and 25%) and PPPI (adjusted to raise the protein levels to 15, 20 and 25%) incorporated in two types of wheat flours (extraction rate 72%); for bread (BrWF) and biscuit (BsWF). Farinograph, Extensograph and Fermentograph of wheat and composite flour doughs were studied. The Farinograms showed that the water absorption values for the composite BrWF/DPPF and BsWF/DPPF were found to range from 65.1 to 65.9 % and 61.6 to 63.7%; dough development time from 4.0 to 5.0 min. and 4.0 to 4.4 min. dough stability from 2.4 to 4.0 and from 2.3 to 4.1 min. for DPPF different ratios